From Revolutionary Fighter to Urban Social Bandit: Kusni Kasdut and the Crisis of State Legitimacy in Indonesia (1945–1980) - Fajar Kurniawan; Tuty Nur Mutia E. Muas; Dwi Mulyatari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This article examines the phenomenon of post-independence urban criminality in Indonesia through a case study of Kusni Kasdut (1925–1980), a former revolutionary fighter who later transformed into an “urban social bandit” in Jakarta during the 1950s–1970s. Drawing upon a social history approach that integrates the theories of social banditry (Hobsbawm), moral economy (Thompson), and living law (Ehrlich), this study analyzes how structural factors—such as economic inequality, rapid urbanization, and the marginalization of former combatants—created conditions conducive to the emergence of criminal figures endowed with a degree of social legitimacy. The analysis of police archives, mass media reports, and oral testimonies reveals a significant discrepancy between the official state narrative, which stigmatized Kusni as a dangerous criminal, and the perception among the urban poor, who regarded him as a protector and a symbol of resistance against injustice. The findings demonstrate that the case of Kusni Kasdut reflects a broader crisis of state legitimacy in the post-colonial period, characterized by the state’s inability to accommodate the aspirations of lower social strata and former revolutionary actors within formal legal structures. This study contributes theoretically by extending the concept of social banditry into a post-colonial urban context and offers a deeper understanding of state–society relations in modern Indonesian history.